Integrated analysis of safety data from 12 clinical interventional studies of plasma‐ and albumin‐free recombinant factor VIII (rAHF‐PFM) in haemophilia A. (25th May 2015) - Shapiro, A. D.; Schoenig‐Diesing, C.; Silvati‐Fidell, L.; Wong, W. Y.; Romanov, V.
<x xml:space="preserve">Abstract</x> Introduction Antihaemophilic factor (recombinant), plasma/albumin‐free method (rAHF‐PFM) is a human recombinant full‐length factor VIII (FVIII) approved worldwide for the control and prevention of bleeding episodes, routine prophylaxis and perioperative management in adults and children with haemophilia A. Aim To evaluate rAHF‐PFM safety [including adverse events (AEs) and inhibitor incidence] from 12 interventional studies spanning >10 years. Methods The study population comprised 418 treated patients (median age = 18.7 years) with FVIII levels ≤2% of normal, including 55 previously untreated or minimally treated patients (PUPs/MTPs) from all rAHF‐PFM phase I–IV studies, excluding observational safety studies. Results Most AEs were non‐serious; only 93 AEs in 45 patients (10.8%) were related to rAHF‐PFM. A total of 106 serious AEs (SAEs) occurred in 69 patients (16.5%); the most common were FVIII inhibitors (4.1%), device‐related infection (1.0%) and pyrexia (0.7%). The 17 SAEs considered related to treatment consisted of FVIII inhibitors in 1 previously treated patient (PTP) (≤5 Bethesda Units [BU]) and 16 PUPs/MTPs [7/55 high titre (>5 BU), 12.7%; 9/55 low titre (≤5 BU), 16.4%]. Overall, the incidence of FVIII inhibitors was 0.36% in PTPs and 29.1% in PUPs/MTPs. No deaths or cases of hypersensitivity related to rAHF‐PFM occurred. Conclusion This integrated safety analysis evaluated the safety and tolerability of rAHF‐PFM in children and adults with moderately severe or severe haemophilia A in all interventional studies completed to date. It was important to review consolidated evidence as some AEs are rare. There were no new safety signals in a wide variety of clinical settings.